The Perinatal Microbiota-Gut-Brain Axis: Implications for Postpartum Depression - Marie Armbruster; Paul Forsythe (Neuroimmunomodulation)
Background: Pregnancy and childbirth are accompanied by widespread maternal physiological adaptations and hormonal shifts that have been suggested to result in a period of vulnerability for the development of mood disorders such as postpartum depression (PPD). There is also evidence of peripartum changes in the composition of the gut microbiota, but the potential contribution of intestinal microbes to the adaptations, or subsequent vulnerabilities, during this period are unknown. Summary: Here, we outline key pathways involved in peripartum adaptations including GABAergic signaling, oxytocin, and immunomodulation that are also associated with susceptibility to mood disorders and present evidence that these pathways are modulated by gut microbes. We also discuss the therapeutic potential of the microbiota-gut-brain axis in PPD and identify future directions for research to help realize this potential. Key Messages: Peripartum adaptations are associated with shifts in gut microbial composition. Disruption of GABAergic, oxytocin, and immunomodulatory pathways may contribute to vulnerability of mood disorders including PPD. These key adaptive pathways are modulated by intestinal microbes suggesting a role for the gut microbiota in determining susceptibility to PPD. More research is needed to confirm relationship between gut microbes and PPD and to gain the mechanistic understanding required to realize the therapeutic potential of microbiota-gut-brain axis in this mood disorder.